2013
DOI: 10.1109/jstars.2013.2251457
|View full text |Cite
|
Sign up to set email alerts
|

Aerial 3D Building Detection and Modeling From Airborne LiDAR Point Clouds

Abstract: Abstract-A fast, completely automated method to create 3D watertight building models from airborne LiDAR point clouds is presented. The proposed method analyzes the scene content and produces multi-layer rooftops with complex boundaries and vertical walls that connect rooftops to the ground. A graph cuts based method is used to segment vegetative areas from the rest of scene content. The ground terrain and building rooftop patches are then extracted utilizing our technique, the hierarchical Euclidean clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
75
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 22 publications
0
75
0
2
Order By: Relevance
“…Kim and Shan [28] also segmented the normal vectors, but they applied a multiphase level set technique. Sun and Salvaggio [29] proposed an automated method to generate 2.5D watertight building models from LIDAR point clouds. Only visual results were presented, so there was no objective evaluation of this method.…”
Section: Related Workmentioning
confidence: 99%
“…Kim and Shan [28] also segmented the normal vectors, but they applied a multiphase level set technique. Sun and Salvaggio [29] proposed an automated method to generate 2.5D watertight building models from LIDAR point clouds. Only visual results were presented, so there was no objective evaluation of this method.…”
Section: Related Workmentioning
confidence: 99%
“…The mostly used plane detection techniques from 3D point clouds are region growing, RANSAC and Hough methods. Vosselman et al (2004) and Sun and Salvaggio (2013) proposed region growing for the segmentation of LIDAR point clouds. Furthermore, interesting and efficient studies have been implemented that segment building roofs (Lafarge et al, 2010;Sampath and Shan, 2010;Kada and Wichmann, 2012;Awrangjeb and Fraser, 2013;Verdie et al, 2015) and man-made scenes (Lafarge and Alliez, 2013;Monszpart et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, surface elevation measurements obtained from airborne LiDAR are quicker and more effective than traditional photogrammetric techniques [17,18]. Since then, a number of studies have been conducted using LiDAR data on the urban 3D building modeling [19][20][21][22][23], urban vegetation identification and green volume estimation [24,25], and solar potential evaluation in the urban area [26][27][28][29][30]. For example, Yu, et al [26] demonstrated that the integration of urban Digital Surface Model (DSM) from LiDAR data and a solar radiation flux model is able to investigate the spatio-temporal variations of solar radiation in downtown Houston.…”
Section: Introductionmentioning
confidence: 99%